Cultural Perceptions of Wild Animals Consumption and Implications for Community Nursing: A Systematic Review - Fadila Lam; Joni Haryanto; Sylvia Dwi Wahyuni (GLOBAL HEALTH SCIENCE GROUP, 2026)
Many communities have long relied on wild animal consumption as part of cultural tradition and food stability. While culturally significant, this practice presents serious public health risks, particularly the transmission of zoonotic diseases through frequent human wildlife interaction in markets lacking proper food safety. These risks demand urgent public health responses that integrate cultural awareness. Community nurses, as key agents in primary health care, play a vital role in addressing these risks through culturally sensitive education and engagement. This study aims to review cultural perceptions of wild animal consumption and analyze their implications for community nursing, especially in strengthening culturally sensitive education and zoonotic risk. This systematic review followed PRISMA guidelines, using five databases (WoS, Scopus, PubMed, ProQuest, ScienceDirect). Study selection was based on PICo criteria, risk of bias assessed with the JBI checklist, and data analyzed thematically. A total of 4,139 records were identified, and 3,940 duplicates were removed before screening. After title, abstract, and full text screening based on the PICo framework, 15 studies met the inclusion criteria. Fifteen studies were included, spanning regions in Asia, Africa, and Latin America. Thematic analysis identified five key themes: (1) cultural beliefs, taboos, and symbolic meanings; (2) traditional uses and medicinal practices; (3) taste preference, nutritional value, and cultural identity; (4) nurse roles in community zoonotic literacy; and (5) socioeconomic drivers and market dynamics. The findings show that cultural beliefs and economic needs often outweigh health concerns in wildlife consumption. Strengthening the role of community nurses in culturally sensitive education and risk communication is essential to reduce zoonotic threats and improve public health responses.